Heat-treated hull flour does not affect iron bioavailability in rats - Hércia Stampini Duarte Martino; Ariela Werneck de Carvalho; Cassiano Oliveira da Silva; Maria Inês de Souza Dantas; Dorina Isabel Gomes Natal; Sônia Machado Rocha Ribeiro; Neuza Maria Brunoro Costa (Archivos Latinoamericanos de Nutrición)
In this study the chemical composition and iron bioavailability of hull and hull-less soybean flour from the new cultivar UFVTN 105AP was evaluated. The hemoglobin depletion-repletion method was used in Wistar rats. Soybean hull flour presented 37% more total dietary fiber and higher content of iron than hull-less soybean flour. The phytate:iron molar ratio, however, was 2-fold lower in the soybean hull flour in compared to the hull-less soybean flour. Animals fed soybean hull flour presented hemoglobin gains similar to those of the control diet group (p>0.05). The Relative Biological Values of hull and hull-less soybean flour were 68.5% and 67.1%, respectively, compared to the control group. Heat-treated soybean hull flour (150ºC/30 minutes) showed high content of iron and low phytate, which favors the iron bioavailability. Thus, the soybean hull flour is a better source of dietary fiber and iron than hull-less soybean flour at comparable bioavailabilities.